The influence of workplace stressors on negative attitudes toward long-term male parental leave: a cross-sectional study in Japan - Ono, Hiromi (Frontiers in Public Health, 2025)
ObjectiveAlthough work–life balance measures have become an important theme in corporate personnel resource management, they have not been thoroughly examined from the perspective of perceived fairness within Japanese organizations. This study developed a model hypothesizing that supervisors’ awareness of interpersonal justice is negatively associated with workplace stressors, while workplace stressors are positively associated with anger through situations that evoke a sense of unfairness related to male parental leave.MethodsA web panel survey was conducted through an Internet research company. Four hundred valid responses were obtained (200 men and 200 women; Mage = 40.25 ± 10.59 years). Participants completed measures of anger, sense of unfairness, workplace stressors, and supervisors’ interpersonal justice.ResultsMen were more likely than women to harbor feelings of anger regarding their male coworkers’ uptake of long-term parental leave. Women were more likely than men to harbor resentment toward male coworkers who take parental leave without fully dedicating themselves to childcare. The goodness-of-fit analysis indicated a good model fit.ConclusionWorkplace stressors are positively associated with anger through a sense of unfairness regarding male parental leave. In Japan, it is easy to think that child-rearing is the responsibility of women, and it is likely that colleagues in the workplace will have negative feelings toward men who take long-term parental leave. In addition, since the interpersonal fairness of supervisors is negatively associated with workplace stressors, it can be concluded that supervisors play an important role in workplaces where men take long periods of parental leave. In the future, if the number of men taking long-term parental leave increases, studies focusing on employees whose male coworkers have taken long-term parental leave will be possible.